Does your HRM matter? A focus on difference between managerial and non-managerial employees. (27th June 2011) - Cho, Seonghee; Woods, Robert H.; Mayer, Karl J.
The purpose of this study was to examine the impact of Human Resource Management (HRM) on organisational performance. This study addressed two measurement challenges suggested by human resource researchers: collecting data separately for managerial and non-managerial employee groups and testing the interrelationships between three organisational performance measures (turnover, labour productivity and growth rate). The structural equation model revealed that the effects of HRM implemented for the managerial employee group were different from the effects of HRM implemented for the non-managerial employees. The primary difference related to the influence of a firm's bottom line. This study also examined the interrelationships among the dependent variables and found that managers' turnover rates reduced by HRM practices increased labour productivity.